Biological Metaphysical Scientism in Addressing the Issue of Altruism and Egoism - N.L. , Varova; S.F. , Denisov; L.V. , Denisova; N.G. , Zenets; L.A. , Maksimenko (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the study is predetermined by the problematization of knowledge about a human in modern philosophic and scientific discourse, a crisis in understanding the morality and moral being of a human, a deficit of altruism, and growing egoism in society. We need to comprehend modern approaches to the study of these ethical aspects, since, on the one hand, there is a contradictory and ambiguous view of altruism and egoism in humanitarian knowledge, and, on the other hand, some apology of naturalism when rapidly developing biological sciences are sure that they can explain this problem. Therefore, this paper aims at studying altruism and egoism and their functional peculiarities in nature and culture from the perspective of <> metaphysical scientism. The leading method of study is a dialectic method. It enables the discovery of the specifics of a new form of scientism, which implies that science (biology) takes the functions of philosophy (metaphysics) and tries to address the issue of altruism and egoism in nature and human activity independently. The novelty of this paper is a critical analysis of important biological concepts and approaches to the explanation of altruism and egoism. We have proved that their conceptualization in a biological discourse is, in fact, a methodological and worldview expansion of biology, which can be qualified as a biological form of metaphysical scientism and denoted by the term “biocracy.” We have revealed two types of such scientism: traditional, where nature is a subject that exceeds a human in its power and wisdom, and innovative, where nature is an object that can be technically modernized up to biotechnological modernization of morality (“ethical eugenics”). We have shown that sociobiology is a kind of reverse toward traditional biological scientism. It implicitly expresses a concern for the modern scale of innovative transformations of human nature and argues that since altruism performs a function of species protection in the animal world, it has the functions of human protection and culture protection in human society. The materials of the paper are of practical and theoretical value for the research of modern tendencies in the development of natural scientific and humanitarian knowledge of altruism and egoism. They enlarge the field of reflection on the bases and methodological peculiarities of scientific and cognitive practices and new forms of culture scientification.